2017
DOI: 10.1158/1078-0432.ccr-17-0246
|View full text |Cite
|
Sign up to set email alerts
|

Pooled Clustering of High-Grade Serous Ovarian Cancer Gene Expression Leads to Novel Consensus Subtypes Associated with Survival and Surgical Outcomes

Abstract: Purpose Here we assess whether molecular subtyping identifies biological features of tumors that correlate with survival and surgical outcomes of high-grade serous ovarian cancer (HGSOC). Experimental Design Consensus clustering of pooled mRNA expression data from over 2,000 HGSOC cases was used to define molecular subtypes of HGSOCs. This de novo classification scheme was then applied to 381 Mayo Clinic HGSOC patients with detailed survival and surgical outcome information. Results Five molecular subtypes… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
99
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 85 publications
(112 citation statements)
references
References 47 publications
(52 reference statements)
9
99
0
4
Order By: Relevance
“…A recent analysis of genotyping accuracy has raised questions about the quality of sequencing-based variant calls in TCGA’s HGSC samples [76] which may affect the findings in Hofree et al [75]. Given the exploratory nature of molecular clustering and limitations of the approaches used, more research is needed about how many underlying molecular subtypes exist [7779] and if they are consistent across populations [80]. …”
Section: Characteristics Of Hgsc Molecular Subtypesmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent analysis of genotyping accuracy has raised questions about the quality of sequencing-based variant calls in TCGA’s HGSC samples [76] which may affect the findings in Hofree et al [75]. Given the exploratory nature of molecular clustering and limitations of the approaches used, more research is needed about how many underlying molecular subtypes exist [7779] and if they are consistent across populations [80]. …”
Section: Characteristics Of Hgsc Molecular Subtypesmentioning
confidence: 99%
“…A recent study reported that women with the proliferative and mesenchymal subtypes benefit from experimental treatment (Bevacizumab) over standard chemotherapy [93], which raises the possibility that similar subtype-specific variations in response to other actively developing therapeutics for EOC, such as PARP inhibition and immune therapies [94,95] might exist. For example, immunoreactive tumors may be good candidates for immunotherapy [79]; an open-label single-arm Phase II trial has been initiated to evaluate efficacy and safety of pembrolizumab anti-PD-1 monotherapy in these cases [96]. For mesenchymal tumors, TGF-beta inhibition may be considered since the TGF-beta pathway is significantly up-regulated compared to other subtypes, which aligns well with other supervised expression studies reporting worse clinical outcomes associated with this pathway [97100].…”
Section: Characteristics Of Hgsc Molecular Subtypesmentioning
confidence: 99%
“…HGSOC molecular subtypes have been independently confirmed by multiple studies [1113]. Our previous studies [13] demonstrated resectability of disease differs by molecular subtype.…”
Section: Introductionmentioning
confidence: 65%
“…Our previous studies [13] demonstrated resectability of disease differs by molecular subtype. HGSOC patients with the mesenchymal (mesenchymal) subtype had the lowest RD0 rates and required more complex surgery to achieve RD ≤1 cm compared to patients with other subtypes of tumors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation